Acinetobacter Prevertebral Abscess: Presenting as Dysphagia in a Diabetic Patient - R. Manmathan; T. Kumanan; J. A. Pradeepan (Case Reports in Infectious Diseases)
Acinetobacter species frequently causes nosocomial infection, particularly in patients receiving invasive ventilation at intensive care units for a prolonged period. Odynophagia is a rare, initial clinical manifestation of prevertebral abscess which subsequently develops when the abscess extends into the retropharyngeal space causing a midline bulge of the posterior pharyngeal wall. Here, we present and discuss a patient with uncontrolled diabetic mellitus who presented with severe odynophagia and dysphagia. He was diagnosed to have prevertebral abscess caused by a rarely reported bacteria, Acinetobacter baumannii.